Obtaining biodegradable plastic from corn cob starch (Zea mays) (Publicaciones en Ciencias y Tecnología, 2023)
A biodegradable plastic was obtained from starch extracted from corn cob. Initially the residue was characterized, the starch was extracted for its characterization and the bioplastic was formulated. An experimental design was proposed, with a variable amount of starch (4, 5, 6 g) and a fixed amount of plasticizer (2 g). Using the results obtained, a second experimental design was established with a fixed amount of starch (5 g) and different amounts of plasticizer (1,50 – 2,50 g). The bioplastic with the best physical appearance and resistance to touch was evaluated in terms of humidity, density, solubility, thickness, mechanical properties and biodegradability. The bioplastic showed 16,69 % humidity; 0,93 g/mL density; 57,79 % solubility in water; 0,63 mm thick and 31,92 % weight loss in the biodegradability test. The most relevant parameters were: low density, high solubility of the material and the percentage of weight lost in the biodegradability test. As a result, the material obtained, if improved, can be used in the manufacture of light products or, as a coating for materials that need to be quickly solubilized.
Keywords: thermoplastic starch; bioplastics; agricultural waste; revaluation of waste